Prospects of Use of Innovative Technologies in Education - Akhmedova Fatima To'raevna (Genius Journals, 2023)
Modern education does not fully meet the needs of the information society. Reform of the education system, transition to a new system, and the need to actively introduce pedagogical innovations. Pedagogical innovation is the process of developing, implementing, testing and evaluating innovations in the field of education that help to effectively achieve these goals. In order to form an innovative educational system, it is necessary to introduce innovative information and technological opportunities into the educational system and study international educational experience. In this article, there are thoughts and opinions about the prospects of using innovative technologies in education
Keywords: educational system; innovative technologies; perspectives